Timing and Localization of Rhamnolipid Synthesis Gene Expression in Pseudomonas aeruginosa Biofilms - Lequette, Yannick (American Society for Microbiology, 2005)
Pseudomonas aeruginosa biofilms can develop mushroom-like structures with stalks and caps consisting of discrete subpopulations of cells. Self-produced rhamnolipid surfactants have been shown to be important in development of the mushroom-like structures. The quorum-sensing-controlled rhlAB operon is required for rhamnolipid synthesis. We have introduced an rhlA-gfp fusion into a neutral site in the P. aeruginosa genome to study rhlAB promoter activity in rhamnolipid-producing biofilms. Expression of the rhlA-gfp fusion in biofilms requires the quorum-sensing signal butanoyl-homoserine lactone, but other factors are also required for expression. Early in biofilm development rhlA-gfp expression is low, even in the presence of added butanoyl-homoserine lactone. Expression of the fusion becomes apparent after microcolonies with a depth of >20 μm have formed and, as shown by differential labeling with rfp or fluorescent dyes, rhlA-gfp is preferentially expressed in the stalks rather than the caps of mature mushrooms. The rhlA-gfp expression pattern is not greatly influenced by addition of butanoyl-homoserine lactone to the biofilm growth medium. We propose that rhamnolipid synthesis occurs in biofilms after stalks have formed but prior to capping in the mushroom-like structures. The differential expression of rhlAB may play a role in the development of normal biofilm architecture.